2007
DOI: 10.1016/j.aquaculture.2007.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intestinal gene expression in Atlantic cod (Gadus morhua) fed standard fish meal or soybean meal by means of suppression subtractive hybridization and real-time PCR

Abstract: Gene expression was studied in Atlantic cod fed two different diets, fish meal (FM) and dehulled and extracted soybean meal (SBM). RNA was isolated from the distal part of the mid-intestine of Atlantic cod and suppression subtractive hybridization (SSH) was employed to screen for genes that showed changes in expression in response to the two dietary treatments. We made a cDNA subtracted library, isolated and sequenced 192 clones. Identification of 157 clones was predicted by BLAST. Most of the clones were prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 50 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…The expression of fabp7, a gene related to fatty acid transport and uptake tended to be up-regulated in liver of sea bass fed ARA0.1, although no differences could be observed among the other dietary treatments. In a similar trial where sea bass were fed diets containing high levels of terrestrial ingredients showed an up-regulation in this gene (Geay et al 2011) and sea bream and cod fed plant-based feed showed up-regulation in fabp2 when fed on more sustainable feeds (Lilleeng et al 2007;Betancor et al 2016b). Additionally, these fish also showed the lowest performance, what could be suggesting that the up-regulation in fabp7 expression may be associated with the lower growth of these fish, which in turn could elicit compensatory mechanisms such as fatty acid mobilization.…”
Section: Discussionmentioning
confidence: 96%
“…The expression of fabp7, a gene related to fatty acid transport and uptake tended to be up-regulated in liver of sea bass fed ARA0.1, although no differences could be observed among the other dietary treatments. In a similar trial where sea bass were fed diets containing high levels of terrestrial ingredients showed an up-regulation in this gene (Geay et al 2011) and sea bream and cod fed plant-based feed showed up-regulation in fabp2 when fed on more sustainable feeds (Lilleeng et al 2007;Betancor et al 2016b). Additionally, these fish also showed the lowest performance, what could be suggesting that the up-regulation in fabp7 expression may be associated with the lower growth of these fish, which in turn could elicit compensatory mechanisms such as fatty acid mobilization.…”
Section: Discussionmentioning
confidence: 96%
“…Soybean meal (SBM) is an excellent plant protein source for fish feed [1]. However, high levels of soybean protein caused a poor growth rate in juvenile Jian carp ( Cyprinus carpio var.…”
Section: Introductionmentioning
confidence: 99%
“…Most notably among these were probably the soyasaponins, phytic acid, lectins and possibly residual levels of protease inhibitors, but other components in SBM could have also played a part as well (Bureau et al . ; Lilleeng, Froystad, Vekterud, Valen & Krogdahl ; Azaza, Kammoun, Abdelmouleh & Kraiem ). Nevertheless, under our test conditions, we did note that some of the depression of chinook salmon growth, feed intake and feed utilization was likely due to the diminished palatability of the diets containing SBM, and that these negative effects were partially reversed by the addition of feed attractants.…”
Section: Resultsmentioning
confidence: 99%